RESOURCE PROVISION FOR THE COMPETITIVE DEVELOPMENT OF FARMING ENTERPRISES IN LVIV REGION: ASSESSMENT OF THE CONDITION AND WAYS OF IMPROVEMENT - Nataliia MARKOVYCH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article is devoted to the necessity of competitive development of farming enterprises in Lviv region to ensure food security both at the state and regional levels in particular. As part of the research, a thorough economic and statistical analysis of their economic activity and resource provision was conducted. It has been found that the farming enterprises of Lviv region are characterized by positive trends of development. In particular, there is a consolidation of farmers by the area of land use, an increase in the number of agricultural products, which had a positive effect on the sale of the main types of agricultural products in the region and beyond. The objective necessity is substantiated for intensive development of cooperation of farming enterprises in Lviv region under conditions of unstable financial and economic situation in the state, which will provide an opportunity to attract investment and innovation resources for their effective development, will ensure production of ecologically clean food products and creation of new jobs. Among the priority directions for the development of farming enterprises in Lviv Region, special attention is focused on the diversification of activities, which is expedient to consider in production, technological and marketing aspects. The study proved that farming enterprises of Lviv region have all the prerequisites for effective business management. Their strategic development should be focused not only on increasing the volume of production, but also on improving the quality of products, which will ensure a high level of their competitiveness on domestic and foreign markets.